Scientific and Technical Tools for Enhancement of Special Treatment Devices - V. V. Mahniboroda; A. A. Gorjachev; A. E. Krasnov (Вестник войск РХБ защиты, 2025)
Highlights- nowadays it is impossible to maintain contaminated vehicles and equipment in special decontamination centers nearthe battle line due to far-ranging precision weapons and drones;- promising on-board sets and special treatment devices should be more independent and powerful than previous ones(IDTS, SST, DK-4) and be able to work directly at the lines of combat contact.Relevance. The main shortcomings on-board special treatment sets and devices are low special treatment rate (0,5–1,0 m2/min),considerable physical efforts during treatment, restricted list of used solvents (formulae) and ways of special treatment, as well as lack of sanitizing for armaments and military and special purpose equipment beyond special decontamination centers.The purpose of the study is to find out possible ways to enhance the efficiency and improve functionality of on-board special treatment devices employed for armaments and military and special purpose equipment and personnel decontamination (sanitizing).Study base sources. The authors have analyzed Russian and foreign open-source data on the topic in question.Method. Analytical method has been employed.Discussion. The analysis of key performance parameters for on-board special treatment devices, employed for armaments and military and special purpose equipment that are operated by the Armed Forces of the Russian Federation and its foreign counterparts has confirmed that either the existing special treatment sets should be improved or a new (unified) on-board special treatment device (set) should be developed which can provide a full special treatment of armaments and military and special purpose equipment with water-based, solvent and foam solutions as well as their sanitizing in summer, autumn and spring.Conclusions. It is worth to develop a promising on-board special treatment set for armaments and military and special purpose equipment if degassing (decontaminating), deactivating, disinfecting solutions and solvents are going to be used. If the foam formulae are going to be used, then a fluid pump should be integrated into the system. It should be able to maintain pressure of at least 14 kgs/m2. Besides, a foam maker should be implemented, the geometrical properties of which can defined with the help of jet blower design theory.